Political Philosophy and the Republican Future : Reconsidering Cicero - Smith, Gregory B. (University of Notre Dame Press, 2018)
Intro -- Half Title -- Title Page -- Copyright -- Dedication -- Contents -- Introduction -- 1. Reflections on the Tradition of Republicanism -- 2. Initial Reflections on Political Philosophy -- 3. Who Was Cicero? -- 4. Cicero on the Nature of Philosophy -- 5. Cicero on Cosmology and Natural Philosophy -- 6. Cicero on Natural Theology -- 7. Cicero on Ethics -- 8. Cicero on Oratory and the Language Arts -- 9. Cicero on Politics -- 10. A Brief Reflection on Nietzsche -- Conclusion: Political Philosophy and the Republican Future -- Notes -- Bibliography -- Index.